Empowering reading and writing skills of primary students with contextual teaching learning approach - Nurfadila, Atika (LADU: Journal of Languages and Education, 2021)
Background: Â To some students, learning Indonesian is very boring especially for students who are not used to read and write.Purpose: This study aims to improve the Indonesian Language Learning Outcomes in grade II students at Sukajadi 02 Elementary School in the Indonesian language subject.Design and methods: This classroom action research refers to the Kemmis and Mc Taggart Model which is commonly referred to as the spiral model consisting of four stages. The planning stage, the action stage, the observation stage, the reflection stageResults: The result showed that through the Contextual Teaching and Learning Approach, learning Indonesian in reading and writing is easier to apply in everyday life that students encounter. It can improve Indonesian language learning outcomes in literacy